COMPONENTS FOR THE DEVELOPMENT OF SPIRITUAL AND MORAL COMPETENCE OF YOUTH (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article discusses the directions of moral education, research on the development of methods and forms of youth education, the analysis of many works written in historical sources in the educational and moral direction of the educational sphere, their integration into the youth essence of the content, at the same time, the direction of educating young people’s a sense of love to Motherland. The upbringing of the younger generation depends, first of all, on the professionalism of the teacher. At the same time, it should be noted that the future and prospects of the country largely depend on the teacher, his level, readiness, dedication, attitude to teaching and upbringing. A teacher can be self-sacrificing only if he has perfect professional ethics and moral qualities. Today, such dedication is more important than ever, increasing the relevance of research in this area.